Pre-Hispanic anthropogenic wetlands in the upper Ica drainage, south-central Andes: dating and context - Lane, Kevin John (2022)
Fil: Lane, Kevin John. Consejo Nacional de Investigaciones Científicas y Técnicas. Universidad de Buenos Aires. Instituto de las Culturas; Argentina